REALIZED INCOME. - Heilman, E. A. (The Accounting Review, 1929)
Abstract The most widely enunciated principle of income determination is that income is realized as the result of the sale of commodities or services. Concepts of "income" and "cost" are two of the most difficult in the whole field of economics and accounting to define in precise terms. Many incomes are earned as the result of the joint operations of two different fiscal periods, since only part of the services for which the final price is paid by the purchaser are performed in each period and part of the costs of furnishing these services falls into each. With the wide diversity found in different enterprises in methods of sale, types of sales contract, methods of production, and in collection methods it would seem reasonable to assume that no single test of income realization would meet all situations with the same degree of satisfaction. Accounting texts admit a number of situations which may need exceptional treatment but the number and importance of these situations is seldom accented and usually there is no open admission that another test of income has been applied. The author points out a wider range of business conditions and situations in which the sale test must be modified or other more adequate tests applied to arrive at the best measure of periodic profits, or of changes in economic positions.